(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the importance of using the works of Eastern thinkers in the education of students. Eastern philosophers, particularly Ibn Sina, Al-Farabi, Al-Farg‘oni, and other great thinkers, proposed important ideas regarding human education in their works. The article discusses the impact of these works on the educational and training process, their role in the moral and spiritual development of students, and how they can be effectively used in the modern educational system. The article also reflects on how the ideas of these thinkers can influence students today, considering historical and cultural contexts.